ASSESSMENT OF THE ALOPURINOL EFFECT ON THE RENAL FUNCTION - Zhdan, V.N.; Tkachenko, M.V.; Babanina, M.Yu.; Volchenko, G.V.; Kitura, Ye.M. (World of Medicine and Biology, 2019)
Hyperuricemia is associated with the development of gout, arterial hypertension and chronic kidney disease. The influence of allopurinol and hypo-uremic therapy on renal function has not been adequately studied, especially in patients with chronic kidney disease who are at increased risk of developing hypersensitivity reactions. The purpose of this study was to determine the effect of allopurinol on the functional capacity of the kidneys in patients with hyperuricemia. This is a retrospective study of a cohort of patients undergoing treatment on the basis of the rheumatologic department and the polyclinics of the Poltava Regional Clinical Hospital. M.V. Sklifosovsky using clinical, pharmacological and laboratory data. Retrospective analysis was conducted from October 2015 to September 2017. The study involved 40 patients with hyperuricemia, which was determined by an increasing in serum uric acid levels higher than 380 mmol / l (an average of ~ 500 mmol / l) who had recently begun therapy with allopurinol for any reason with a verified response to treatment. The comparison group consisted of 40 patients with hyperuricemia without a clinical manifestation who were not treated with allopurinol. All patients were divided by age, sex and glomerular filtration rate (GFR). Patients receiving allopurinol at an average dose of 250 mg / day (SD, 78) showed an increase in GFR of 11.8 ml / min (95% confidence interval, a dose of 4.7-11.8 mg / day , P = 0.01) than in the control group. It was found that the treatment effect depended on the baseline level of GFR, which is evidenced by a more significant therapeutic effect in patients with lower baseline GFR (P = 0.004). In the allopurinol treatment group, the lower endpoint of creatinine was 0.12 mg / dL (95% confidence interval, 0.003-0.20 mg / dl, P = 0.04) than in the control group of patients at baseline creatinine and age. Among the patients studied, two cases of adverse events were reported. Treatment of patients with hyperuricemia with allopurinol with an average duration of 15 months has led to a significant improvement in renal function in a cohort of men with hyperuricemia. Clinicians should take into account the potential benefits of allopurinol in the treatment of patients with hyperuricemia, especially those who need support and control of kidney function.
Keywords: hyperuricemia; renal function; allopurinol